The Influence of Information Technology Toward Interest In Utilization of The Virtual Learning Environment - Wildoms Sahusilawane; Lilian Sarah Hiariey (Journal of Education and Learning (EduLearn), 2018)
This research aims at examining the effect of Ease, Affect, Flexibility and Accessibility of information technology on utilizing virtual learning environment at Universitas Terbuka. The population of the research consists students of Bidikmisi scholarship in Non Basic Education program of Accounting that include of 145 respondents. The sampling method is purposive sampling with 141 eligible samples. The questionnaires are measured with Correlation and Multiple Regression analysis that covers descriptive statistics, reliability test and validity test. Classical Assumption Test which includes multcollinearity test is later conducted. Hypothesis testing and discussion are presented at the end. Result of research with t test or partially indicate that, variable of ease of use have positive relation and have significant influence to interest of utilization of virtual learning environment, t test result for accessibility variable have positive relation and no significant effect to interest of utilization of virtual learning environment. The result of the research on the affect variable has a positive relationship and has a significant effect on the interest of utilizing the virtual learning environment. While the flexibility variable shows have a negative relationship and no significant effect on the interest of utilization of virtual learning environment.